112k views
2 votes
When solving equation which is the best first step to begin to simplify the equation -2(x+3)=-10

2 Answers

5 votes

Answer:

If we divide the equation with -2 in both sides

Subtract 3 in both sides

thats how i worked it out

Explanation:

User Daniele Orlando
by
6.4k points
3 votes

Answer:

Explanation:

Alright, lets get started.

The given equation is :


-2(x+3)=-10

If we divide the equation with -2 in both sides


(-2(x+3))/(-2)=(-10)/(-2)


(x+3)=5


x+3=5

Subtract 3 in both sides


x+3-3=5-3


x=2

So, the first step of simplifying equation is divide equation with -2. : Answer

Hope it will help :)

User Inquisitor Shm
by
6.6k points